2004
DOI: 10.1524/ract.92.3.133.30487
|View full text |Cite
|
Sign up to set email alerts
|

An EXAFS and TRLFS study of the sorption of trivalent actinides onto smectite and kaolinite

Abstract: SummaryThe structure parameters of the Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 19 publications
6
83
0
Order By: Relevance
“…A linear correlation between the hydrolysis constants of metal ions and their sorption onto montmorillonite was reported by Bradbury and Baeyens (2006). Surface complexes on kaolinite (Am(III), Cm(III), U(VI)) were identified by means of TRLFS and EXAFS (Stumpf et al, 2004;Křepelová et al, 2008). The presence of HA enhanced the sorption of Am(III), Cm(III) and U(VI) in the pH range below 5 and decreased it at higher pH values (Samadfam et al, 2000;Křepelová et al, 2006).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…A linear correlation between the hydrolysis constants of metal ions and their sorption onto montmorillonite was reported by Bradbury and Baeyens (2006). Surface complexes on kaolinite (Am(III), Cm(III), U(VI)) were identified by means of TRLFS and EXAFS (Stumpf et al, 2004;Křepelová et al, 2008). The presence of HA enhanced the sorption of Am(III), Cm(III) and U(VI) in the pH range below 5 and decreased it at higher pH values (Samadfam et al, 2000;Křepelová et al, 2006).…”
Section: Introductionmentioning
confidence: 86%
“…A layer consists of a single sheet of SiO 4 tetrahedra combined into hexagonal rings, with a superimposed dioctahedral gibbsite type sheet of edge sharing octahedra (Strunz and Nickel, 2001). Some of the important papers reporting on the sorption of radiotoxic contaminants onto kaolinite are: Aksoyoglu et al, 1991;Kohler et al, 1992;Niitsu et al, 1997;Samadfam et al, 2000;Sakuragi et al, 2002;Payne et al, 2004;Stumpf et al, 2004;Křepelová et al, 2006Křepelová et al, , 2008Amayri et al, 2008;Buda et al, 2008;Kautenburger andBeck, 2008 and. The sorption ability of the various metal ions onto kaolinite was found to be strongly dependent on their oxidation state, thereby showing moderate (Np(V)), high (Am(III), Cm(III)) or very high sorption (Th(IV), Pu(IV)).…”
Section: Introductionmentioning
confidence: 99%
“…Some structural data on the sorption of trivalent actinides and lanthanides for carbonate free systems have been obtained by means of spectroscopic techniques. The sorption of Eu(III) and Cm(III) on montmorillonite, illite and kaolinite has been investigated by time resolved laser fluorescence spectroscopy (TRLFS) as a function of pH in the absence of CO 2 [20,21]. The structure of Am(III) sorbed on smectite and kaolinite at varying pH was analyzed using combined TRLFS and X-ray absorption spectroscopy (XAS).…”
Section: Resultsmentioning
confidence: 99%
“…The structure of Am(III) sorbed on smectite and kaolinite at varying pH was analyzed using combined TRLFS and X-ray absorption spectroscopy (XAS). However, the XAS data alone could not unambiguously prove the inner-sphere character of the sorption of Am(III) on these clay minerals, since only the first Am−O shell could be obtained from the data [21]. For lanthanide/actinide carbonate-clay mineral systems, no reliable thermodynamic and structural data are available.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, both clay and granite-based repository concepts implement a backfill of bentonite, a type of montmorillonite. For these reasons, many studies have evaluated actinide sorption onto clay minerals including montmorillonite (e.g., Bachmaf and Merkel, 2011;Bertetti et al, 1998;Chisholm-Brause et al, 1992Kowal-Fouchard et al, 2004;Lujaniene et al, 2007;McKinley et al, 1995;Pabalan and Turner, 1997;Pabalan et al, 1998;Stumpf et al, 2004;Tsunashima et al, 1981;Turner et al, 1998); illite (Bradbury and Baeyens, 2009;Lujaniene et al, 2007Lujaniene et al, , 2010, and kaolinite (Bachmaf and Merkel, 2011;Stumpf et al, 2004). Many studies have evaluated uranyl sorption onto smectites and have found that sorption occurs both by ion exchange and by surface complexation (Bradbury and Baeyens, 2005;Kowal-Fouchard et al, 2004;Turner et al, 1996).…”
Section: Actinide Element Oxidation Statesmentioning
confidence: 99%